An Exploratory Interview Study About Teacher Strategies in Encouraging Secondary Students Participation in EFL Writing Classroom - Elya Kristian Fernando (IJET (Indonesian Journal of English Teaching), 2022)
This research paper exploring teachers' strategies in encouraging EFL secondary students to participate in writing classes. The researcher conducted research in one of the public schools in district Karawang and appointed one of the teachers at the school as a participant. In this research, researcher employed qualitative design with the research method Interview Study. The researcher collects data using Semi-structured Interviews and documentation analysis. In addition, the data obtained were analyzed by researcher in several stages so that the findings could be identified. The findings show participant uses six strategies in encouraging EFL secondary students to participate in writing classes, namely, Building Motivation and Confidence in Learning Writing, Using English as a Classroom Language, Using Technology in Learning Writing, Mandatory Using Dictionary, Interweaving Assessment and Teaching, Proper Time Management.